Design and development of an impeller wind turbine - Ahmed Younus Qasim (School of Mechatronic Engineering, 2013)
This research focuses on the design of a special frame impeller type vertical axis wind turbine with scoop vane shape to get maximum force from the wind. The objectives are:- to increase the power coefficient and efficiency of the turbine and analyze its performance by increasing the drag factor of the blade, reducing the negative torque produced by the frame rotating in the opposite direction of the wind and compare the results with those obtained from other types of wind turbine model; to fabricate a model of a new designed wind turbine; to carry out experimental study of the wind turbine model using wind tunnel.